Heart targeting nanoparticles via tannic acid modification for cardiac tissue regeneration - Carvalho, Cláudia Sofia Cordeiro (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019